Enhanced automotive engine cooling systems - a mechatronics approach. (20th February 2004) - Wagner, J.; Paradis, I.; Marotta, E.; Dawson, D.
Internal combustion spark ignition and diesel engines are used worldwide to meet society's need for transportation and mobile power generation. The cooling system is responsible for thermal management of the engine block, under-hood components, and passenger compartment. The majority of production vehicles use a thermostatic valve and belt-driven water pump whose operation is fixed with respect to the coolant temperature and the engine speed, respectively. However, transient engine operation, environmental changes, and product life-cycle events should be accommodated by the cooling system to enhance thermal efficiency while maintaining engine performance and vehicle driveability. In this paper, a mechatronic thermostatic valve is presented for a continual on-line motor and CVT-based mechanical water pumps are discussed in terms of adjustable fluid flow rates. The operation of current thermostat valves are introduced followed by the design of an ECU controlled solenoid or dc servo-motor thermostat actuator. A multi-node resistor-capacitor nonlinear thermal model is presented to estimate the thermal behaviour of cylinder components. The proposed control algorithm manages the coolant flow rate to regulate engine temperature while offsetting possible abnormal combustion effects, oil lubrication issues, and anticipatory driving demands. Numerical results are presented and discussed to demonstrate the validity and functionality of the automotive mechatronic system for thermal regulation.